Response of furrow irrigated raised bed planted maize (Zea mays) to different moisture regimes and herbicides treatments under semi-arid conditions - RAWAL, SANDEEP; DHINDWAL, A S; PUNIA, S S (The Indian Journal of Agricultural Sciences, 2018)
An experiment was conducted on furrow irrigated raise bed (FIRB) planted maize at Hisar, during kharif season of 2013 and 2014, in split plot design with three replications. Four moisture regimes, viz. irrigation applied at an interval of 80 mm, 120 mm, 160 mm and 200 mm cumulative pan evaporation (CPE) were evaluated in main plot and five weed control treatments, viz. weed free, weedy check (control), pre emergence application of pendimethalin at 1000g/ha, pre emergence application of atrazine at 750 g/ha and post emergence application of tembotrione at 120 g/ha in sub plots. Above normal well distributed rainfall (564 mm) was received during 2013 maize crop season lead ingto comparatively higher consumptive use of water and less water productivity as compared to 2014 season, in which only 212 mm rainfall was received. Irrigation applied at 80 mm CPE resulted in significantly higher growth and yieldparameters, grain, straw and biological yield while highest water productivity was achieved with 120 mm CPE intervalirrigation. Among weed control treatments, growth and yield parameters, grain yield and the water productivity washighest in weed free which was statistically comparable with the application of atrazine, 750 g/ha (pre emergence)or tembotrione, 120 g/ha (post emergence) with lowest density and dry weight of weeds.